Analisis Kondisi Awal Perkuliahan Mahasiswa Pendidikan Fisika Dalam Rangka Mengembangkan Bahan Ajar Statistika Pendidikan Fisika Menggunakan Model Problem Solving - Dewi, Wahyuni Satria; Afrizon, Renol (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
This research is important as a solution to the problems faced by most students in the Physics Education Statistics course. The problem in this study is that students have not been able to solve the statistical problems correctly, becausetheir ability in solving the statistical problems given by lecturers in the class is low. This is also caused by abstract and difficult material to understand by students. In addition, the source books used in lectures are only in the form of a reference books and have not been oriented to problem-solving steps related to daily life such as educational issues. This study aims to analyze the needs in developing teaching materials of Physics Education Statistics with Problem Solving model. This research is an early stage of research and development using ADDIE model in the form of analysis phase. Data collected by using questionnaire given to physics education students listed on semester July-December 2017. Data analysis technique used in the form of descriptive statistical analysis. The results show several things; 1) The teaching materials used by the lecturers in the course have not been entirely appealing for the students to be reviewed independently, 2) the task that has been given by the lecturer are able to motivate the students to solve it, 3) lecturers have provided guidance to students in solving problems, but not yet using varied method, 4) the material presented in the lecture has not been fully understood by the students, as some of the material is still abstract, 5) Only a small percentage of students can answer statistical problems quickly and correctly, 6) Students have enough basic math skills, but only some students can use the statistical formula correctly, and 7) Students who are able to correctly depict distribution and graphic curves are sufficient. The conclusion of this study is the need of development of teaching materials Statistics of Physics Education using problem solving model.